Sulfonated alumina: A suitable catalyst for furfural biomass building-block valorization through multicomponent reactions (2021)
Sulfonated alumina was synthetized and tested for the first time in furfural valorization through a multicomponent reaction for the preparation of a nitrogenated heterocyclic compound containing the furan substructure. Ten polysubstituted heterocycles, belonging to the dihydropyrimidinones (thiones) and 1,4-dihydropyridines, were obtained with very good yields (70% – 85%) using the tandem methodology and green reaction conditions.  The catalyst was easily separated from the reaction medium, giving a high yield in the reusability studies. Green metrics were analyzed in order to consider the reaction suitability.